Effects of a Permanent Soil Cover on Water Dynamics and Wine Characteristics in a Steep Vineyard in the Central Spain. Issue 13 (September 2020) - Marques, MJ; Ruiz-Colmenero, M; Bienes, R; García-Díaz, A; Sastre, B
The study of alternative soil managements to tillage, based on the evidence of climate change in the Mediterranean basin, is of great importance. Summer and autumn are critical seasons for soil degradation due to the high-intensity, short-duration storms. Vineyards are vulnerable, especially on steep slopes. The particular effects of storms over the years under different soil conditions due to different management practices are not frequently addressed in the literature. The aim of this study was to examine the differences between runoff and soil moisture patterns influenced by 2 treatments: traditional tillage (Till) and a permanent cover crop. A shallow-rooted grass species Brachypodium distachyon (L.) P. Beauv. with considerable density coverage was selected as cover crop. This annual species was seeded once in the first year and then allowed to self-seed the following years. Tillage was performed at least twice in spring to a 10- to 15-cm depth and once in late autumn at a depth of 20 to 35 cm. Rainfall simulation experiments were performed, 1 year after treatments, using high-intensity rainfall on closed plots of 2 m 2, located in the middle strips of the vineyard with different treatments. The effects of simulated rainfall experiments were determined in 3 different moments of the growth cycle of cultivar: (1) in summer with dry soils, (2) in early autumn with moderate soil moisture, and (3) in autumn with wet soils. During the 2-year trial, the soil moisture level in the soil upper layer (0-10 cm) was higher for Till treatment (14.1% ± 2.4%) compared with that for cover crop treatment (12.3% ± 2.0%). However, soil moisture values were more similar between treatments at 35 cm depth (12% ± 1%), with the exception of spring and autumn; in spring, water consumption in the cover crop treatment was the highest, and the moisture level at 35 cm depth was reduced (12%) compared with that for Till treatment (13%). In autumn, in cover crop treatment, higher water infiltration rate in soils led to higher soil moisture content at 35 cm (11%) compared with that of Till treatment (10%). The effects of simulated rainfall experiments on runoff and infiltration under different soil conditions and management practices vary seasonally. Runoff was significantly higher in summer for cover crop treatment (11%) as compared with that for Till management (1%), but significantly lower (3%) with wetter soils than for Till treatment (22%) in autumn. Thus, the simulation experiments with wet soils using cover crops produced higher infiltration rates and, consequently, the higher soil moisture content in the following days. The difference between seasons is attributed to the greater porosity of soil under Till treatment in summer, which resulted from the shallow plowing (10-15 cm depth), carried out to reduce moisture competition between weeds. The effect of traditional spring plowing was short-lived. The infiltration of water increased by cover crop treatment as compared with tillage in autumn both before and after ripping. Management practices did not influence wine parameters, as no significant differences were found between wine organoleptic characteristics in the duo-trio wine tastings, similarly, no differences were found for alcoholic degree, acidity, reduced sugars, and pH; however, a trend for a positive increase in polyphenol contents was noticed. Therefore, properly managed to avoid water shortages, cover crops can be recommended for soil protection in semi-arid environments.